MD Simulations Revealing Special Activation Mechanism of Cannabinoid Receptor 1 - Wu, Yiran; Li, Xuanxuan; Hua, Tian; Liu, Zhi-Jie; Liu, Haiguang; Zhao, Suwen (Frontiers in Molecular Biosciences, 2022)
Cannabinoid receptor 1 (CB1) is a G protein-coupled receptor that is gaining much interest for its regulating role in the central nervous system and its value as drug target. Structures of CB1 in inactive and active states have revealed conformational change details not common in other GPCRs. Here, we performed molecular dynamics simulations of CB1 in different ligand binding states and with mutations to reveal its activation mechanism. The conformational change of the 'twin toggle switch' residues F2003.36 and W3566.48 that correlates with ligand efficacy, is identified as a key barrier step in CB1 activation. Similar conformational change of residues 3.36/6.48 is also observed in melanocortin receptor 4, showing this 'twin toggle switch' residue pair is crucial for the activation of multiple GPCR members.